Arah, Kendala dan Pentingnya Diversifikasi Konsumsi Pangan di Indonesia (Forum Penelitian Agro Ekonomi, 2016)
EnglishFood consumption diversification (FCD) is possible to develop in Indonesia, a country consisting of thousands of islands with various social and economic circumstances, and diversified soil fertility and regional potentials. This paper aims to describe direction, constraints and importance of FCD. The FCD policy was designed to decrease rice consumption and began since early 1960’s, but the reality shows that rice as staple food in all provinces tends to intensify. People tend to dislike local food, such as corn and tubers, and they tend to enjoy global food, such as noodle. Some factors constraining FCD are: (1) rice is more tasteful and easier to cook, (2) concept of eating in which people have to eat rice in their menus, (3) rice as superior commodity is available abundantly and its price is cheap, (4) low community’s income, (5) low technology processing and less promotion of non rice food, (6) overlapped food policies, and (7) wheat import policy and intensive noodle products promotion. It is important to have a successful program on FCD because it will not improve human resource only, but it will also have positive impact on food security, farmers’ income, food agro industry, and saving foreign exchange.IndonesianIndonesia yang terdiri dari ribuan pulau dengan keragaman sosial, ekonomi, kesuburan tanah dan potensi daerah, memungkinkan untuk tercipta diversifikasi konsumsi pangan (DKP). Makalah ini bertujuan untuk menganalisis arah, kendala dan pentingnya DKP. Kebijakan DKP bertujuan untuk menurunkan konsumsi beras sudah dirintis sejak awal tahun 60-an, namun kenyataan menunjukkan posisi beras sebagai pangan pokok di semua provinsi semakin kuat. Pangan lokal seperti jagung dan umbi-umbian ditinggalkan masyarakat, sebaliknya pangan global seperti mi semakin banyak digemari. Beberapa faktor yang menjadi penghambat DKP adalah karena rasa beras lebih enak dan mudah diolah, konsep makan, merasa belum makan kalau belum makan nasi, beras sebagai komoditas superior ketersediaannya melimpah dengan harga yang murah, pendapatan masyarakat masih rendah, teknologi pengolahan dan promosi pangan non beras masih rendah, kebijakan pangan yang tumpang tindih, serta kebijakan impor gandum dan promosi produk mi yang gencar. Keberhasilan kebijakan DKP penting tidak hanya untuk meningkatkan kualitas sumberdaya manusia, tetapi juga berdampak positif pada ketahanan pangan, pendapatan petani dan agroindustri pangan serta menghemat devisa.
Keywords: diversification; food consumption; constraints; Indonesia; diversifikasi; konsumsi pangan; kendala